An action control perspective of evaluative conditioning. Issue 1 (1st January 2019) - Walther, Eva; Blask, Katarina; Halbeisen, Georg; Frings, Christian
ABSTRACT: Attitudes are at the core of many topical issues, and a meeting point for research and discussion. This pervasiveness is not surprising given an attitude's utility in reducing the complexity of the environment into relatively simple likes or dislikes of stimuli. How attitudes are formed is usually addressed by means of evaluative conditioning (EC). EC has been addressed from a traditional cognitive and a functional account. In this article, we present a different perspective on EC, which is situated in action control research. This perspective tries to take advantage of the strengths of both existing EC accounts by focusing on those cognitive processes that enjoy high levels of experimental control and that are necessary to explain how stimuli find their way into mental processing and ultimately into an evaluative response. Implications of this action control based account for EC research in specific and for attitude research in general are discussed.